Remarks at the G20 Finance Ministers and Central Bank Governors Meeting - Malpass, David (World Bank, Washington, DC, 2021)
David Malpass, President of the World Bank, discussed the World Bank climate change action plan, debt and the DSSI, and resource needs for IDA countries.